2023
DOI: 10.3389/fnut.2022.1084589
|View full text |Cite
|
Sign up to set email alerts
|

Current status of research and gaps in knowledge of geophagic practices in Africa

Abstract: This article synthesises current knowledge and identifies research gaps on the still intriguing aspects of the subject of geophagy as practised in Africa. Despite the voluminous research literature that exists on the subject, geophagy in Africa is still a largely misunderstood phenomenon. Although the practice is not confined to any particular age group, race, gender, or geographical region, in Africa it is most commonly recorded among pregnant women and children. Till now, the precise aetiology of geophagy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 135 publications
(209 reference statements)
0
4
0
Order By: Relevance
“…In Tanzania, Nyanza et al [39] and Young et al [53] reported the presence of toxic heavy metals such as lead, mercury and arsenic in their respective areas of study. Such studies and report have also been done by other researchers including Molale and Eze (2023) [36] , Davies [13] , Orisakwe [40] and others, hence making the assessment of health hazards of great importance. Therefore, this study focuses on identifying mineral constituents of the geophagic soil collected from different parts in Tanzania (Morogoro, Njombe and Mwanza regions) in 2019 and assessing the associated health risks to the consumers.The analysis was done in 2019–2020 at the University of Dar es Salaam and Ardhi University.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In Tanzania, Nyanza et al [39] and Young et al [53] reported the presence of toxic heavy metals such as lead, mercury and arsenic in their respective areas of study. Such studies and report have also been done by other researchers including Molale and Eze (2023) [36] , Davies [13] , Orisakwe [40] and others, hence making the assessment of health hazards of great importance. Therefore, this study focuses on identifying mineral constituents of the geophagic soil collected from different parts in Tanzania (Morogoro, Njombe and Mwanza regions) in 2019 and assessing the associated health risks to the consumers.The analysis was done in 2019–2020 at the University of Dar es Salaam and Ardhi University.…”
Section: Introductionmentioning
confidence: 82%
“…In parts of Europe, geophagy was reported between 18th and 19th century where this habit was again associated with chlorosis in young children [51] . Geophagy has been practiced in Africa and Asia where it has played different roles in medicine, spiritual, religious rituals, psychological, nutritional and in cosmetics [13] , [19] , [51] . In Africa, geophagy has been reported in many countries including Nigeria, Sierra-Leone (Hunter 1993), Zambia [46] ,Tanzania [53] , Ghana [38] South Africa [19] , [32] , Chad [27] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Ground soil has been noted to be severely contaminated with multiple heavy metals [20,26,40]. Despite consistent evidence of higher toxic chemical element exploration from practicing geophagy, the motivations and drivers of the practice are complex [41],…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria specifically, some natives, such as the Igbo and Tiv women, have certain weird beliefs which propel them to consume 'Eko', especially pregnant women. One of which is that geophagic clay contributes to the overall nutritional status of pregnant women (Davies, 2023). Traditional doctors known as "dibias" in the Igbo-speaking part of Nigeria also make use of this clay in the treatment and cure of different diseases (Izugbara, 2003).…”
Section: Introductionmentioning
confidence: 99%